If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 8(x + -2) = (3x + 1) * 4 + 1 Reorder the terms: 5 + 8(-2 + x) = (3x + 1) * 4 + 1 5 + (-2 * 8 + x * 8) = (3x + 1) * 4 + 1 5 + (-16 + 8x) = (3x + 1) * 4 + 1 Combine like terms: 5 + -16 = -11 -11 + 8x = (3x + 1) * 4 + 1 Reorder the terms: -11 + 8x = (1 + 3x) * 4 + 1 Reorder the terms for easier multiplication: -11 + 8x = 4(1 + 3x) + 1 -11 + 8x = (1 * 4 + 3x * 4) + 1 -11 + 8x = (4 + 12x) + 1 Reorder the terms: -11 + 8x = 4 + 1 + 12x Combine like terms: 4 + 1 = 5 -11 + 8x = 5 + 12x Solving -11 + 8x = 5 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. -11 + 8x + -12x = 5 + 12x + -12x Combine like terms: 8x + -12x = -4x -11 + -4x = 5 + 12x + -12x Combine like terms: 12x + -12x = 0 -11 + -4x = 5 + 0 -11 + -4x = 5 Add '11' to each side of the equation. -11 + 11 + -4x = 5 + 11 Combine like terms: -11 + 11 = 0 0 + -4x = 5 + 11 -4x = 5 + 11 Combine like terms: 5 + 11 = 16 -4x = 16 Divide each side by '-4'. x = -4 Simplifying x = -4
| Y=5/2x-5 | | 4/(1-x)=5/(1+x) | | c^2-9c= | | 13/(2x-3)=11(x+3) | | 13/2x-3=11x+3 | | -15t^2+60t+10=0 | | 4x-2.1=-6.3+1.9x | | 3x^2+4x-17=0 | | (x+1/x)^2-5(x+1/x)+6=0 | | 5/6x+1+3 | | 3j-7j=12 | | (x-9)(5x+12)=0 | | 121=r^2 | | 625=r^2 | | 324=r^2 | | 2x+5=3+5x | | 6-5=4x+1 | | 6x+5=4x+1 | | 5805.86=3.14r^2 | | 4j-9j+3=-3 | | (x-7)(y-5)= | | (5x)=(3x+28) | | (3x-1)(3-8x)= | | y=4(7x+100) | | y=1/2+5(0,3) | | (8k-9)(3k-7)= | | 36^1/2 | | x-49=57 | | 9x+6x-12=-7x+2x-12+5 | | -21=y/4 | | 9x-6=3x+6 | | -b=19 |